Cultural Influences on Listening Comprehension. (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
Cultural influences significantly impact listening comprehension, shaping how individuals interpret spoken language and contextual meaning. This article explores the role of culture in listening comprehension, focusing on challenges such as idiomatic language, high-context versus low-context communication, accents, and cultural references. It highlights strategies to address these barriers, including exposure to diverse listening materials, teaching cultural competence, emphasizing contextual understanding, and encouraging active listening. The discussion underscores the importance of fostering cultural awareness in learners and communicators to improve listening comprehension and promote effective cross-cultural communication.